Anthracnose Severity and Annual Bluegrass Quality as Influenced by Nitrogen Source. (16th August 2017) - Schmid, Charles J.; Clarke, Bruce B.; Murphy, James A.
Abstract : Anthracnose (caused by Colletotrichum cereale Manns sensu lato Crouch, Clarke & Hillman) of annual bluegrass [ABG, Poa annua L. f. reptans (Hausskn.) T. Koyama] turf is a destructive fungal disease that has been shown to be more severe under nitrogen (N) deficiencies. Little is known about the effect of soluble N source on this disease. A 3‐yr field study was initiated in 2010 to evaluate the effect of soluble N source on anthracnose severity and to determine if N source alters the effect of N frequency on this disease during midseason on an ABG turf maintained at 3.2 mm. Nitrogen treatments were applied at 4.9 kg N ha −1 every 7 or 14 d (frequency factor) as solutions of ammonium sulfate, ammonium nitrate, urea, calcium nitrate, or potassium nitrate. Both N frequency and N source affected disease severity throughout 2010, 2011, and 2012. In general, soluble N applied at 4.9 kg N ha −1 every 7 d reduced disease compared with N applied at the same rate every 14 d. Of the N sources, potassium nitrate provided the greatest reduction in disease severity over the 3‐yr study, whereas ammonium sulfate treatments resulted in the greatest disease severity. Soil pH was also influenced by N source, with ammonium sulfate treatments resulting in the lowest soil pH (most acidic), and potassium nitrate consistently producing the highest soil pH (most basic) throughout the study. Potassium nitrate also greatly increased soil K. This study has shown that anthracnose severity on ABG putting green turf is influenced by N source, and that low‐rate applications of potassium nitrate every 7 d were most effective at reducing disease severity under moderately acidic soil conditions and moderate to low soil K levels.